STRATEGI KESANTUNAN DALAM DEBAT CAWAPRES PERIODE 2014 s.d. 2019 DI TV ONE BERDASARKAN PENDEKATAN BROWN DAN LEVINSON: STRATEGI KESANTUNAN DALAM DEBAT CAWAPRES PERIODE 2014 s.d. 2019 DI TV ONE BERDASARKAN PENDEKATAN BROWN DAN LEVINSON - Nur Ainun Makkiyah; Taufik Nurhadi (Buana Bastra, 2015)
This research is motivated by the fact that the use of languageis polite to the people who have an important role for Indonesia it is very important due to the smoothness and harmony and to establish intimacy between the narrator and the opponent. The formulation of the problem in this research is "How politeness between Hatta Rajasa and Jusuf Kalla on TV One in the candidate Vice President debate period2014-2019 based on the approach of Brown and Levinson? ". The aim or the purpose is to describe the linguistic politeness Hatta Rajasa and Vice President Jusuf Kalla in the debate vice president debate on TV One based approach Brown and Levinson. This study used a qualitative approach. The data in this study were obtained from the candidate Vice President debate sentences containing linguistic politeness strategies according to Brown and Levinson. Source of data in this study, candidate vice president debate. Data collection techniques in this research that usesrefer methods, tapping techniques, and use advanced techniques is (SBLC). Based on the findings and the discussion has been described in chapter IV, it can be concluded that politeness strategies according to Brown and Levinson include (1) Bald-on Strategy (Without Strategy), (2) Positive Politeness Strategy (familiarity), ( 3) Negative Politeness Strategy (Formalities), and (4) Off-record Politeness Strategy (Strategy of indirect or fuzzy.